An Optimized Two-Herb Chinese Food as Medicine Formula Reduces Cisplatin-Induced Nephrotoxicity in the Treatment of Lung Cancer in Mice - Le Shi; Yang Shu; Xiangdong Hu; Waheed Akram; Jun Wang; Shuang Dong; Biaobiao Luo; Jiuliang Zhang; Sheng Hu; Xiaohua Li; Xuebo Hu (Frontiers Media S.A., 2022)
Chemotherapy is considered a most effective way to treat cancer. However, it is very common that chemotherapy causes unbearable mental and physical side effects to cancer patients, which ultimately reduces the patients' confidence of overcoming diseases and compromises the treatment of chemotherapy. Cisplatin (DDP), a widely used anticancer agent for various types of cancers, also damages nontumor cells and tissues, which are mostly related to the activation of the inflammation pathway. Previously, we have discovered a few rational formulas of food as medicine materials that reduced systemic inflammation in in vitro and in vivo models. Hence, this study reports the ability of an optimized traditional Chinese anti-inflammatory formulation capable of synergizing the antitumor effect of DDP in vitro and in vivo. More significantly, by formulation of two anti-inflammatory herbal medicine, the Chrysanthemum × morifolium (Ramat.) Hemsl [Asteraceae] and Lonicera japonica Thunb [Caprifoliaceae] with a mediator Glycyrrhiza uralensis Fisch. ex DC [Fabaceae], a best formula relieved the kidney damage imposed by DDP. Treatments of various combinations of major chemical components of the three herbs also exhibited a similar trend for lowering the DDP-induced nephrotoxicity; however, contrary to that of the formula of herbal extracts, all chemical formulas could not recover the body weight and food intake of the tumor-bearing mice treated by DDP. Our findings suggested that the therapeutic index of DDP-based chemotherapy was able to be improved by minimizing toxicities from the two-herb formula to inhibit the inflammation in mouse tumor models and DDP-induced acute kidney injury mouse models.